The Influence of Instructional Leadership, Work Climate, and Work Motivation on Teacher Performance (A Study of Junior High School Teachers in Kelumpang Hilir District, Kotabaru Regency) - Dody Alfayed; Aslamiah Aslamiah; Sutarto Hadi (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
Teacher performance is a key factor in improving the quality of learning and achieving educational goals. This performance is influenced by the instructional leadership of the principal, the work climate, and teacher motivation. Suboptimal instructional leadership and an unfavorable work climate have the potential to reduce teacher motivation and performance. This study aims to analyze the description of the principal's instructional leadership, work climate, work motivation, and teacher performance, as well as to examine the direct and indirect effects of instructional leadership and work climate on teacher performance through work motivation. This study uses a quantitative approach with a population of all junior high school teachers in Kelumpang Hilir District, Kotabaru Regency, totaling 102 people who were sampled using the total sampling technique. Data were collected using questionnaires, then analyzed descriptively with SPSS and inferentially using SmartPLS 4 through outer model and inner model testing. The results show thsat descriptively, all variables are in the high to very high category. Inferentially, instructional leadership and work climate have a positive and significant effect on teacher motivation and performance, with contributions of 66.7% and 74.9%, respectively. Work motivation was found to act as a mediating variable in the relationship between instructional leadership and work climate on teacher performance, with indirect contributions of 4.9% and 1.5%, respectively. These findings confirm that effective instructional leadership and a conducive work climate can increase teacher work motivation, thereby impacting the continuous optimization of teacher performance.